Melatonergic system‐based two‐gene index is prognostic in human gliomas. Issue 1 (20th November 2015) - Kinker, Gabriela S.; Oba‐Shinjo, Sueli M.; Carvalho‐Sousa, Claudia E.; Muxel, Sandra M.; Marie, Suely K. N.; Markus, Regina P.; Fernandes, Pedro A.
Abstract: Gliomas, the most common primary brain tumors in adults, are classified into four malignancy grades according to morphological features. Recent studies have shown that melatonin treatment induces cytotoxicity in glioma‐initiating cells and reduces the invasion and migration of glioma cell lines, inhibiting the nuclear factor κ B (NF κ B) oncopathway. Given that C6 rat glioma cells produce melatonin, we investigated the correlation between the capacity of gliomas to synthesize/metabolize melatonin and their overall malignancy. We first characterized the melatonergic system of human gliomas cell lines with different grades of aggressiveness (HOG, T98G, and U87MG) and demonstrated that glioma‐synthesized melatonin exerts an autocrine antiproliferative effect. Accordingly, the sensitivity to exogenous melatonin was higher for the most aggressive cell line, U87MG, which synthesized/accumulated less melatonin. Using The Cancer Genome Atlas RNAseq data of 351 glioma patients, we designed a predictive model of the content of melatonin in the tumor microenvironment, the ASMT:CYP1B1 index, combining the gene expression levels of melatonin synthesis and metabolism enzymes. The ASMT:CYP1B1 index negatively correlated with tumor grade, as well as with the expression of pro‐proliferation and anti‐apoptotic NF κ B target genes. More importantly, the index was a grade‐ and histological type‐independent prognostic factor. Even when considering only high‐grade glioma patients, a low ASMT:CYP1B1 value, which suggests decreased melatonin and enhanced aggressiveness, was strongly associated with poor survival. Overall, our data reveal the prognostic value of the melatonergic system of gliomas and provide insights into the therapeutic role of melatonin.